Predictors of undernutrition and anemia among children aged 6–24 months in a low-resourced setting of Ghana: a baseline survey. Issue 1 (19th June 2020) - Appiah, Collins Afriyie; Mensah, Faustina O.; Hayford, Frank E. A.; Awuuh, Vincent A.; Kpewou, Daniel Edem
Abstract : Purpose: The purpose of this study was to identify the predictors of child undernutrition and anemia among children 6–24 months old in the East Mamprusi district, Northern region, Ghana. Design/methodology/approach: This cross-sectional study recruited 153 children and their mothers. Weight, height and hemoglobin levels of the children were measured. A structured questionnaire based on the World Health Organization's indicators for assessing infant and young child feeding practices was used to collect data on parents' socioeconomic status, household characteristics, hygiene and sanitation practices, mothers' knowledge on feeding practices such as child's meal frequency and dietary diversity and child morbidity within the past two weeks. Predictors of child nutritional status were determined using multinomial logistic regression analysis. Findings: Underweight in the children was significantly predicted by maternal knowledge on protein foods (AOR = 0.045, p = 0.008), time of initiation of complementary feeding (AOR = 0.222, p = 0.032) and maternal age (AOR = 9.455, p = 0.017). Feeding child from separate bowls (AOR = 0.239, p = 0.005), minimum meal frequency per child's age (AOR = 0.189, p = 0.007) and time of initiation of complementary feeding (AOR = 0.144, p = 0.009) were significant determinants of stunting among the children. Exclusive breast feeding (AOR = 7.975, p = 0.012) and child's past morbidity (AOR = 0.014, p = 0.001) significantly contributed to anemia among the children. Research limitations/implications: This is a cross-sectional study and cannot establish causality. The small sample size also limits the generalizability of study findings. However, findings of the study highlight factors which could potentially influence the high rate of child undernutrition in the study setting. Practical implications: This study identifies determinants of undernutrition in the East Mamprusi district, an underresourced area in Ghana. This information could inform the development/reformulation of locally sensitive key messages and targeted intervention strategies to curb the high levels of child undernutrition in the East Mamprusi district of Ghana. Originality/value: This study identifies maternal care practices as key potential drivers of undernutrition in a low-resource setting known for high prevalence of child undernutrition. It suggests insight for large-scale studies on the predictors of child undernutrition in Northern Ghana and other resource-poor settings.